Morphological ontogeny of Oribatula pannonica (Acari, Oribatida, Oribatulidae), and comments on some species of Oribatula Berlese - Seniczak, Stanisław; Ivan, Otilia; Seniczak, Anna (Zootaxa, 2024)
The morphological ontogeny of Oribatula pannonica Willmann, 1949 is described and illustrated. Most prodorsal setae of juveniles are of medium size, and bothridial seta is clavate. The larva has 11 pairs of gastronotal setae, including h2, most are of medium size and barbed, nymphs have 13 pairs (p3 absent), of which most are short and smooth. Basal excentrosclerites are present at nine pairs of gastronotal setae (c1, c2, d-, l-series, h1) in the larva, and at 12 pairs (c1, c2, d-, l-, h-series, p1) in the nymphs. The morphology of adult O. pannonica is compared with congeners with 13 pairs or an unknown number of notogastral setae.